Comparative Analysis of the Mitochondrial Genomes of Nicotiana tabacum: Hints Toward the Key Factors Closely Related to the Cytoplasmic Male Sterility Mechanism - Wang, Ruyi; Cai, Xunhui; Hu, Shengnan; Li, Ying; Fan, Yanjun; Tan, Siqiao; Liu, Qiyuan; Zhou, Wei (Frontiers in Genetics, 2020)
Background: Cytoplasmic male sterility (CMS) is a complex phenomenon of plant sterility that can produce nonfunctional pollen. It is caused by mutation, rearrangement or recombination in the mitochondrial genome. So far, the systematic structural characteristics of the mitochondrial genome changes from the maintainer lines to the CMS lines have not reported in tobacco. Results: The mitochondrial genomes of the flower buds from both CMS lines and maintainer lines of two Nicotiana tabacum cultivars (YY85, sYY85, ZY90 and sZY90) were sequenced using the PacBio and Illumina Hiseq technology, and several findings were produced by comparative analysis based on the de novo sequencing. (1) The genomes of the CMS lines were larger, and the different areas were mostly non-coding regions. (2) A large number of rearrangement regions were detected in the CMS lines, with many translocation regions. (3) Thirteen gene clusters were shared by four mitochondrial genomes, among which two of the gene clusters, nad2-sdh3 and nad6-rps4, were far from each other in the CMS lines. (4) Thirty-three protein-coding genes were conserved in four mitochondrial genomes. However, nad3 was detected one additional copy in the maintainer lines, and the four candidate genes (atp6, cox2, nad2 and sdh3) were revealed sequence differences. Importantly, the evolutionary tree based on the four genes could be used to distinguish the CMS lines and the maintainer lines well for the sequenced tobacco mitochondrial genomes. (5) Sixteen CMS-specific open reading frames (ORFs) were found, three of which (orf91, orf115b and orf100) were previously reported. (6) The intensity differences of the protein-protein interaction in ATP6 were further verified using the yeast two-hybrid analysis. Conclusions: Although the majority of sequences, genes and gene clusters were shared by the mitochondrial genomes of the maintainer and the CMS lines in tobacco, extensive structural variations identified with comprehensive analysis based on the mitochondrial genomes, including rearrangement, gene order, the mitochondrial genome expansion and shrinkage events, might be related to CMS. Additionally, candidate protein-coding genes and CMS-specific ORFs were closely associated with the CMS mechanism. The verification experiments of one of candidate genes were performed, and the validity of our research results was supported.